A Decade of Legally Practicing the Environmental Assessment Tool - Uprety, Batu Krishna (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
Two and half-decades of experience in implementing environmental assessment (EA) tools through policies and legislations have contributed to integrating environmental aspects into development projects in Nepal. The Enforcement of Environment Protection Act (EPA) of 1996 and the Environment Protection Rules (EPR) of 1997 have expanded the application of EA tools for the prescribed proposals. After the enforcement of EPA and EPR, the government has approved the EIA reports of 72 projects. In 2006 alone, EIA reports of 22 projects were approved. In general, however, approval of EIA reports has no meaning unless they are effectively implemented. The benefits of EA could be realised after environmental monitoring and auditing that helps to know the level of compliance and effectiveness of mitigation measures. This article outlines the causes of delay decision and major initiatives taken to make the EA more effective, realistic and practical. Hydro Nepal: Journal of Water, Energy and Environment Vol. 1, No. 2(2008) pp. 13-16